Facile Preparation of Gold Nanoparticles Silica Composite Film Embedded in Anodized Aluminium Oxide-Glass Substrate - Mohamad Azani Abd Khadir Jalani; Juan Matmin; Siew Ling Lee; Syaza Azhari; Mohd Hayrie Mohd Hatta; Nur Fatiha Ghazalli (USIM PRESS, 2024)
Malaysian Journal of Science, Health & Technology (MJoSHT) Volume 10 Issue 1 Page (19-25)